The Implementation of a Life Skills-Oriented Participatory Learning Strategy to Improve Reading and Writing Skills - Nurwahidah, L S (KnE Social Sciences, 2018)
The key to improving the quality of women’s lives in rural areas is improving their reading and writing skills. This strategy emphasizes the needs and considers local potentials. To obtain an accurate conclusion, this research used a quantitative approach with a single subject A-B-A design. The data collection techniques used were tests, observations, and interviews. The subjects consisted of three mothers of varying ages and with a range of writing and reading skills. The research results proved that the activities of reading and writing as performed by mothers in Panawuan village, Garut regency were variously related to the purpose, duration, teacher, and time. From this research, we obtained a general picture that the implementation of participatory learning strategies could run well and be effective in improving reading and writing skills, although there were still inhibiting factors in this implementation. To develop the results of this research, it is necessary to try to develop longer post-literacy research by prioritizing local potential and needs and/or by coupling this with the use of their mother tongue as the language of instruction. In addition, there should also be an attempt to implement this in urban environments with different professions, environmental potential, and needs. Keywords: reading and writing skills, participatory learning strategies, life skills